Anais Do XIX Congresso Da Sociedade Ibero-Americana De Gráfica Digital 2015 2015
DOI: 10.5151/despro-sigradi2015-sp90284
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Building envelope using parametric and algorithmic processes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The Cambridge Dictionary [33] defines an algorithm as a "set of mathematical instructions or rules that, especially if given to a computer, will help to calculate an answer to a problem". Oxman [25] considers algorithmic design as the coding of explicit instructions to generate digital forms, while Queiroz and Vaz [34] state that algorithmic design allows the user to design directly through code manipulation. Similarly to the parametric process in this research, algorithmic modelling is a modelling process that acts as an algorithmic design process.…”
Section: Research Objectivesmentioning
confidence: 99%
“…The Cambridge Dictionary [33] defines an algorithm as a "set of mathematical instructions or rules that, especially if given to a computer, will help to calculate an answer to a problem". Oxman [25] considers algorithmic design as the coding of explicit instructions to generate digital forms, while Queiroz and Vaz [34] state that algorithmic design allows the user to design directly through code manipulation. Similarly to the parametric process in this research, algorithmic modelling is a modelling process that acts as an algorithmic design process.…”
Section: Research Objectivesmentioning
confidence: 99%
“…When it comes to facades, Queiroz et al (2015) explored, through parametric design, the distribution of shading devices with different geometric attributes on the envelope of a building in Recife. The simulations showed that the distribution of shading devices on the envelope conferred a certain uniformity of solar incidence.…”
Section: Parametric Design Applications For Energy Efficiencymentioning
confidence: 99%
“…Regarding benefits of parametric design, the main ones mentioned were: analysis of alternatives and immediate feedback (Sheikh and Gerber, 2011;Das and Dutt, 2012;Felippe et al, 2015;Queiroz et al, 2015;Anton andTǎnase , 2016, Touloupaki andTheodosiou, 2017); optimization of solutions by genetic algorithms (Gerber and Lin, 2013); dynamic control over multiple parameters (Touloupaki and Theodosiou, 2017); interdisciplinary design environments (Anton and Tǎnase, 2016), and reduction of errors caused by manual processes (Felippe et al, 2015).…”
Section: Bim and Parametric Design Benefits For Buildings' Energy Effmentioning
confidence: 99%
“…In recent years, generative design has made many useful explorations in design, evolutionary calculation and morphogenesis. Although there are definitional controversies [1], they all emphasise the evolutionary process of design, such as the application of design procedures (DP) to the exploration of column forms [2], the generation of design systems for energy-efficient building solutions [3], using parameters and algorithmic processes to allocate shading equipment [4], etc. However, the exploration of generative design on the architectural layout is rare.…”
Section: Introductionmentioning
confidence: 99%